A Walk in the Night with Zhuangzi : Musings on an Ancient Chinese Manuscript. - Huang, Kuan-yun (SUNY Series in Chinese Philosophy and Culture Ser., 2023)
A complete translation and analysis of "All Things Flow into Form" (Fan wu liu xing), a recently discovered manuscript from the Warring States period (481-221 BCE).